On the Spaces of Guerre Moderne: The French Army in Northern Algeria (1954–1962) - Samia Henni (Footprint)
The French Colonial War of Anti-Algerian Independence (1954–1962) is widely regarded as the precursor of civil-military counterinsurgency operations, and thereby of the rhetorical Global War on Terror of today. Its theories, known as the guerre moderne, were secretly transferred to North and South America in the sixties. Since the invasion of Iraq in 2003, however, the United States and other Western powers have overtly expressed their interest in French military practices in Algeria, but seldom in the fields of architecture and territorial planning.